Vulnerability assessment of upland communities in Sibalom Natural Park, Antique, using capital-based approach - Saldajeno, Pilar B. (2012)
Agricultural-based livelihoods of most upland communities are vulnerable to risks associated with climate variability and extremes. These risks are compounded by the different socio-economic and biophysical factors concerning livelihoods. It is imperative that assessment of these vulnerabilities be comprehensive to capture the different significant factors and an alternative method is the use of capital-based approach. Three upland communities in Sibalom Natural Park (SNP) were surveyed and key informants were interviewed to assess the communities' social vulnerability. Social vulnerability index (SVI) was computed from the thirty nine indicators representing human, natural, social, financial, and physical capital assets. There is high vulnerability owing to the low capital assets among households, thus, it is vital to strengthen education, access to government support, regularity and quality of income sources; increase crop production; and provide basic infrastructure such as roads and bridges to minimize vulnerability.
Keywords: Uplands - Conservation